Proposed performance management system for project based organization in pt telekomunikasi indonesia, tbk (case study: digital project) - Alberto, Richard; Ros Bangun, Yuni (The Indonesian Journal of Business Administration, 2018)
Abstract. (Introduction) To achieve the vision of King of Digital in The Region and achieve the 2018 Striving Triple Double Digit Growth target (Revenue, Net Income and EBITDA), PT Telkom needs to change the organizational structure which is still based on the structure-based organization. The flexible organizational structure will provide acceleration to create new and innovative digital products and services and can no longer rely on legacy products. Changes in flexible organizational structure of technology has become a very important thing to be done to win the competition in the digital era. (Methods)One of the main aspects of flexible organization is designing performance management system (PMS) that can motivate employees to be able to (Results) provide innovations in digital products and services. (Conclusion) Fit PMS will help member of digital project to explore his innovation and make impact to digital business.Keywords: design, digital, , organization, project, performance